2019
DOI: 10.1016/j.compag.2019.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Camellia japonica cultivars and chemometric models: An interlaboratory study

Abstract: Camellia japonica is a valued plant since ancient times throughout the world mostly due to their ornamental flowers. It has a high number of cultivars, with very similar phenotypic and genotypic characteristics which are difficult to discriminate, being some of them often rare and with a high price at the market. Their discrimination is mostly done through visual inspection of the morphologic characteristics which is a hard and inefficient task. Spectroscopic techniques had already been used for taxonomic purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Among them, near-infrared (NIR) and mid-infrared (MIR) spectroscopy are probably the most publicized technologies [27][28][29][30]. These two technologies can provide detailed structural information on sample properties and composition at the molecular level [31][32][33][34]. Like human fingerprints, the infrared spectrum of any substance has to be unique [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, near-infrared (NIR) and mid-infrared (MIR) spectroscopy are probably the most publicized technologies [27][28][29][30]. These two technologies can provide detailed structural information on sample properties and composition at the molecular level [31][32][33][34]. Like human fingerprints, the infrared spectrum of any substance has to be unique [31].…”
Section: Introductionmentioning
confidence: 99%
“…Like human fingerprints, the infrared spectrum of any substance has to be unique [31]. This is the reason for NIR and MIR spectral fingerprints can be applied to identify or classify different samples [31][32][33][34]. In the case of medicinal plants, chemical constituents and their ratios of biochemicals of different species can vary substantially [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…tries [30,33]. These plants present vast phenotypic differences, more than 32,000 known cultivars [39], and possess a great economical value due to its beautiful flowers [30].…”
mentioning
confidence: 99%
“…The study of its genetic structure revealed that these plants maintain high levels of genetic diversity and a high evolutionary potential which makes them less susceptible to environmental stresses [28]. This could explain with these species are also well adapted in many other countries [33].…”
mentioning
confidence: 99%